DEVELOPMENT OF MATHEMATIC LEARNING QUALITY THROUGH THE IMPLEMENTATION OF PROBLEM BASED LEARNING MODEL BY USING STRUCTURED SCAFFOLDING TO GRADE VIII-1 STUDENT AT SMPN 3 MAKASSAR - Nur Hasmah Hasan (Universitas Negeri Makassar, 2016)
This research is a classroom action research that aims to improve the quality of learning mathematics through problem based learning model application using scaffolding structured learner VIII-1 SMP Negeri 3 Makassar. What is meant in this case is (i) To improve the quality of mathematics learning process through the implementation of problem based learning models using structured learner scaffolding VIII-1 SMP Negeri 3 Makassar; (Ii) To improve the quality of learning mathematics through problem based learning model application using scaffolding structured learner VIII-1 SMP Negeri 3 Makassar. Data collection techniques used through observation sheets, learning achievement test and questionnaire responses of learners. Provision of actions conducted in two cycles. Data analysis was done by the analysis of quantitative and qualitative data. The results of this study indicate that (i) adoption of a model problem based learning by using scaffolding structure can improve the quality of the learning process of mathematics learners VIII-1 SMP Negeri 3 Makassar with the achievement of the following indicators: (1) Increased percentage of activity learners from before implementation to the first cycle of 71.25% is in the category fairly and to the second cycle of 83.25% are in either category; (2) The increase in the change of attitude of learners prior to the implementation of the first cycle with a score of 2.41 are in good category and to the second cycle with a score of 3.43 in the category very well. (Ii) adoption of a model problem based learning by using scaffolding structure can improve the quality of mathematics learning on the learner VIII-1 SMP Negeri 3 Makassar are already shown by the increasing mathematics achievement of students before action to the first cycle with the percentage of completeness in the classical amounted 38.46% are in the poor category with an average score of 69.92 learners ideal score of 100 and is in a category simply by standard deviation of 15.10 to the second cycle with the classical completeness percentage of 79.49% in the good category with an average score of 78.77 learners ideal score of 100 and are in categories with a standard deviation of 11.78